Pengaruh Pelayanan Fiskus, Sanksi Perpajakan, Dan Penerapan E-Filing Terhadap Kepatuhan Wajib Pajak Di KPP Pratama Batam Selatan - Sinaga, Eli Fransiska; Ompusunggu, Hermaya (Jurnal Ilmiah Wahana Pendidikan, 2023)
Tax is one of the biggest income in every country, especially in Indonesia. This observation aims to analyze the influence of service tax authorities, tax sanctions and the application of e-filing on taxpayer compliance at KPP Pratama Batam Selatan. This study used a descriptive and quantitative statistical approach with a sample of 100 respondents and used a questionnaire as a data collection instrument. From the analysis of the data, the results show that service tax authorities have an effect on taxpayer compliance with t count (2,623) > t table (1,984), tax sanctions have an effect on taxpayer compliance with t count (2,987) > t table (1,984) and the application of e-filing effect on taxpayer compliance with t count (4.898) > t table (1.984). Simultaneously the results of the F test for service tax authorities, tax sanctions and the application of e-filing have an effect on taxpayer compliance with an F count (28.985) > F table 2.699).